Avaliação da eficiência de três linhagens de leveduras na produção de bebida alcoólica fermentada de cupuaçu (Theobroma grandiflorum Schum) - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
Cupuassu (Theobroma grandiflorum Schum) is the most popular and favorite fruit from Amazon, due to the taste and aroma. The pulp “in natura” is white, like cream and sour taste. It is used to produce juice, jam, ice cream and liqueur. The pulp can be use to prepare fermented alcoholic beverage with alcoholic content from 4 to 14% (v/v), produced by fermentation of ripe and healthy fruit, by action of yeasts. The aim of this study was to evaluate the efficiency of three strains of yeasts isolated from Amazon, belonging to the culture collection of North and Northeast Network, to elaborate fermented alcoholic beverage, using cupuassu as raw material and to select the best strain to produce cupuassu fermented alcoholic beverage. Three S. cerevisiae strains (DPUA 1172, 1175 and DPUA DPUA 1210) were tested for fermentative capacity, ethanol tolerance, flocculation capacity and production of hydrogen sulfide (H2S). The beverages were analyzed for soluble solids (° Brix), pH, total and volatile acidity, sulfur dioxide, ethanol, residual sugar and sensorial analysis. Among three yeasts, two (DPUA 1210 and DPUA 1175) showed oenological properties. At the end of fermentation, the ethanol concentration produced by yeast DPUA 1210 and 1175 were 11.25 ° GL and 10.33 ° GL, respectively. The DPUA 1210 yeast (Ef = 83,60%) showed better efficiency than DPUA 1175 (Ef = 80,55%). From the selected strain were made two types of beverages: one with a sugar concentration of 8.45 g / L, which is characterized like a “semi-dry wine” and the other one with 21.01 g / L of sugar, indicating a “soft wine”. The sensorial analysis, made with these two types of beverages indicated that in all attributes, both beverages were well accepted, reaching good or excellent, respectively, in the global evaluation.
Keywords: Fermentação alcoólica; Microrganismos; Frutas da Amazônia; Alcoholic fermentation; Microorganisms; Fruits of the Amazon; CIÊNCIAS AGRÁRIAS: CIÊNCIA E TECNOLOGIA DE ALIMENTOS: CIÊNCIA DE ALIMENTOS